MODELS OUTPUT SETS OF SMALL AND MEDIUM ENTERPRISES IN THE SUBJECTS OF THE RUSSIAN FEDERATION - JULIA SEMENOVNA Pinkovetskaia (Мир новой экономики, 2018)
In the conditions of economic crisis is relevant the problem of accelerated development small and medium entrepreneurship. Support for this sector of the national economy requires scientific substantiation ofthe necessary resources. The aim of the study, the results of which are given in the paper was the modeling of the dependency of output small and medium entrepreneurship from investment in fixed assets and wagesof employees using production functions. As the object of research were considered sets of small and medium enterprises in the subjects of the Russian Federation. The paper describes the methodology and results of theevaluation degree of two-factor production functions. The modeling conducted on the basis of official statisticaldata for 2014 year on the subjects of the country. Proven high quality approximation of these data using the achieved production functions. The practical importance of research consists that its results can be used tojustify the need for investments and labour resources, monitoring of the level of development small and medium enterprises in the regions of the country.